Policies of educational inclusion in Chile: Three critical nodes - Verónica López; Pablo Gonzalez; Dominique Manghi; Paula Ascorra; Juan Carlos Oyanedel; Silva Redón; Francisco Leal; Mauricio Salgado (Arizona State University, 2018)
Having achieved the coverage challenges following compulsory policies and a financing system via demand subsidy conditioned to enrollment and attendance, but faced with the scenario of school segregation, Chile has set itself the goal of advancing towards the right to an inclusive education and of quality. In this article we identify and analyze three critical nodes that affect the possibilities of achieving this goal: a) a tension between the logic of integration and educational inclusion, b) a market-based model that does not consider public values, and c) a new educational architecture, based on the logic of individual accountability, which places the possibility of educational improvement in individual incentive systems tied to the achievement of high performance tests. We discuss the need to address and unlock these nodes through transdisciplinary research.